Innvielse til læreryrket En analyse av praksislæreres veiledningssamtaler - Reier Jensen, Andreas (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"How do you really become a skilled teacher? And what role should guidance play in the education of tomorrow's teachers? This theme is explored through a study of experienced practitioners' formalized counseling conversations with teacher students. The most important questions in the book are about how the practice teacher and teacher conduct conversations. Concretely, the question is: What is the content of the counseling interviews? How are the teacher students evaluated? How is the consequences of the counseling discussions understood? The guide being examined contains a step by step pedagogy. First, the teacher's student must learn to control, master and reflect on the social space both the classroom and the counseling conversation are. This is described as an overall moral and regulatory discourse. This discourse forms the basis for the teacher's next step - which is the actual teaching. The teacher's student must therefore master two discourses - one regulatory discourse and one teaching discourse - in order to become a skilled teacher. In addition, he or she must adapt to the regulatory discourse in the counseling conversation. The latter discourse represents in this book an initiation ritual for the teaching profession. This ritual gives the practice teacher control over the dedication, while limiting the room for maneuver in the counseling conversation. "